1997
DOI: 10.1002/(sici)1097-0347(199705)19:3<188::aid-hed4>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three prophylactic antibiotic regimens in clean-contaminated head and neck surgery

Abstract: Background Although appropriate perioperative antibiotic prophylaxis has significantly reduced wound infection rates in clean‐contaminated head and neck surgical procedures, controversy still remains regarding the optimal antibiotic regimen. Methods In this prospective, double‐blind clinical trial, 159 patients were randomized to receive amoxicillin‐clavulanate, clindamycin plus gentamicin, or cefazolin intravenously up to ½ hour before surgery and at 8‐hour intervals for an additional three doses. Results An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 15 publications
1
42
1
Order By: Relevance
“…Cole et al [5] found that the presence of laryngectomy stoma is also significant. It has been stated that the existence of a stoma preoperatively may lead to colonization of secretions and infection [30]. Moreover the presence of a stoma may have led to colonization of the wound and favoured infection persistence, with selection of resistant pathogens (infection on foreign body).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cole et al [5] found that the presence of laryngectomy stoma is also significant. It has been stated that the existence of a stoma preoperatively may lead to colonization of secretions and infection [30]. Moreover the presence of a stoma may have led to colonization of the wound and favoured infection persistence, with selection of resistant pathogens (infection on foreign body).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the postoperative hospital stay is dramatically increased [18,23,30,34]. Alterations in quality of life and poor cosmetic results are evident, but no study has been carried out to analyse specifically these subjective parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The Antimicrobial Agents Committee of the Surgical Infection Society of the United States of America recommends cefazolin for prophylaxis in clean-contaminated head and neck surgery, although it has Gram-positive aerobic coverage only (Rodrigo et al, 1997). To date, it remains the mainstay for prophylaxis in cleancontaminated head and neck surgery (Shinagawa et al, 2003;Rodrigo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several prospective, randomized, double-blinded studies have been conducted in attempts to determine the optimal regimen of antimicrobial prophylaxis for clean-contaminated head and neck surgery [7,8,21,[52][53][54]. The specific antimicrobial agent and the duration of prophylaxis have been examined.…”
Section: Choice Of Antibioticmentioning
confidence: 99%
“…Similar efforts to determine the pathogenicity of gramnegative isolates from wound culture have been less clear. Although one study was able to demonstrate a reduction in the incidence of wound infection by adding gram-negative coverage to the prophylactic antibiotic regimen [56], other studies have not [52,53,59]. Current consensus is that in most cases, isolation of gram-negative aerobes from wound culture represents colonization.…”
Section: Choice Of Antibioticmentioning
confidence: 99%